2003
DOI: 10.1614/p2002-145
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen management will influence threshold values of green foxtail (Setaria viridis) in corn

Abstract: Environmental legislation may impose limitations on the quantity of nitrogen (N) used in corn production on the basis of soil type and ground water flow. If N rates are reduced, this might influence the relative competitiveness of weed species. Therefore, the objectives of this research were to develop a surface response model to provide estimations of the effect of differing N rates on threshold values of green foxtail in corn and to use this model as a theoretical framework for hypothesis testing. Field expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…Corn grain yield in the absence of green foxtail [Setaria viridis (L.) Beauv. ] increased with the addition of N (Cathcart and Swanton 2003), but in the presence of variable densities of green foxtail that emerged with the crop, corn grain yield decreased by an Table 2. average of 18 to 23% despite increasing rates of N. In the presence of green foxtail, corn yield reductions were 35 to 40% with 0 kg N ha 21 , were only 20 and 8% at 100 kg N ha 21 , and were 12 to 17% at 200 kg N ha 21 , for 1999-2001, respectively (Cathcart and Swanton 2003. These losses indicated that green foxtail was not as responsive to available N as corn and amount of yield loss decreased as N rate increased.…”
Section: ---------------------------------------------Mm ------------mentioning
confidence: 99%
“…Corn grain yield in the absence of green foxtail [Setaria viridis (L.) Beauv. ] increased with the addition of N (Cathcart and Swanton 2003), but in the presence of variable densities of green foxtail that emerged with the crop, corn grain yield decreased by an Table 2. average of 18 to 23% despite increasing rates of N. In the presence of green foxtail, corn yield reductions were 35 to 40% with 0 kg N ha 21 , were only 20 and 8% at 100 kg N ha 21 , and were 12 to 17% at 200 kg N ha 21 , for 1999-2001, respectively (Cathcart and Swanton 2003. These losses indicated that green foxtail was not as responsive to available N as corn and amount of yield loss decreased as N rate increased.…”
Section: ---------------------------------------------Mm ------------mentioning
confidence: 99%
“…Higher available N after lentil than wheat has also been generally reported (Grant et al 2002). Several weeds are heavy users of available N (Moyer and Dryden 1977;Moyer et al 1979;Blackshaw et al 2003;Cathcart and Swanton 2003); therefore, similar available N after all crops with no herbicides can be attributed to nitrogen use by weeds. Total crop plus weed biomass (data not presented) was not affected by herbicide (P > 0.05), suggesting that a similar amount of N was required to produce weed and crop biomass.…”
Section: Effect Of Residues From Ethalfluralin and Metribuzin On Follmentioning
confidence: 99%
“…Fertilization management is one of these practices; it can change the interference between culture and competitor (Liebman and Janke, 1990;Ditomaso, 1995). Studies reported that N increased the competitive capacity of weeds over cultures (Santos et al, 1998;Dhima and Eleftherohorinos, 2001;Andreasen et al, 2006) or that it benefited cultures in the presence of weeds (Mishra and Kurchania, 2001;Evans et al, 2003;Cathcart and Swanton, 2004;Abouziema et al, 2007).…”
Section: Introductionmentioning
confidence: 99%